2006
DOI: 10.3349/ymj.2006.47.4.587
|View full text |Cite
|
Sign up to set email alerts
|

Time for Change: The State of Emergency Medical Services in South Korea

Abstract: Trauma is the leading cause of death among people younger than 40 years of age in South Korea. This demographic represents the productive members of Korean society, yet little is being done to correct this growing problem. The preventable death rate in Korea is estimated to be approximately 60%, which is unacceptable given Korea's growing economy and available resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Korean paramedic students were taught current ACLS concepts and guidelines (6,7). They underwent the same rigorous ACLS lectures and hands-on training as developed by the AHA.…”
Section: Methodsmentioning
confidence: 99%
“…Korean paramedic students were taught current ACLS concepts and guidelines (6,7). They underwent the same rigorous ACLS lectures and hands-on training as developed by the AHA.…”
Section: Methodsmentioning
confidence: 99%
“…In order to do this, introduction of the trauma system is essential, and Korea has also started to build a trauma system including the establishment of a regional trauma center [3,6]. The system should be improved at the pre-hospital stage and the transfer stage as well as a process to efficiently operate the trauma system and make continuous efforts to supplement it.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported in 2006 found that the cost of production loss per trauma death was about 350 million KRW. However, the preventable mortality rate in Korea trauma patients was 50.4% in 1998, 39.6% in 2004, and 32.6% in 2007, respectively [3], to improve this, the Korea government started a serious trauma specialization center project from 2012 to support the installation of the regional trauma center [4]. In Korea, emergency medical services (EMS) may be crucial role in fire department-or hospital-based ground transportation of trauma patients in both rural and urban areas, with few exceptions (accidents or disasters occurring on a mountain or on the sea) [5].…”
Section: Introductionmentioning
confidence: 99%